Developing Inventory Management in Hospital - Duangpun Kritchanchai; Watcharaphong Meesamut (International Journal of Supply Chain Management, 2015)
Single inventory policy has been applied to entire types of drugs in hospitals, despite several different drug and demand characteristics. Shortages regularly occur, which may affect patients lives, especially when vital drugs are being administered to them. However, hospitals cannot store a large amount of every drug because of limited space and budget. The objective of this study was to develop a hospital inventory management system to minimise the total inventory costs, while maintaining patient safety levels. This study is concerned only with the medicines that have a high consumption value and took place in a large public hospital in Thailand. The most suitable policies are proposed for each drug category with the best performance obtained.The historical demand is classified by drug characteristics, consumption value and clinical importance, as well as the demand characteristics. We applied it and compared it with the current inventory policy (Min/Max), and inventory policies from previous studies, in order to investigate the most suitable inventory policy for each drug category and demand characteristic. The study found that a single inventory management system cannot be effectively applied for all medicines. This is because there are also categories of medicines characterised by their value and clinical importance. This is called the ABC/VEN classification. The inventory management in hospitals should be fitted to drug categories and demand characteristics, which are quite unique in the healthcare supply chain and are different from those applied to [KK1]general manufacturing. [KK1]I put this in to highlight the differences